Sweet dreams, Sarah [book with audioplayer] - Kirkfield, Vivian (Findaway World, LLC, 2019)
"Sarah E. Goode was one of the first African-American women to get a US patent. Working in her furniture store, she recognized a need for a multi-use bed and through hard work, ingenuity, and determination, invented her unique cupboard bed. She built more than a piece of furniture. She built a life far away from slavery, a life where her sweet dreams could come true"--Amazon.com.